НЕКОТОРЫЕ АСПЕКТЫ РАЗВИТИЯ КРЕАТИВНЫХ КАЧЕСТВ У БУДУЩИХ ПЕДАГОГОВ-ХУДОЖНИКОВ (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This article is devoted to revealing the aspects of developing creative qualities of future visual art teachers. From a scientific and pedagogical perspective, it examines how students in the field of Visual Arts and Engineering Graphics education can form creative skills in design, information, organizational–communicative, and experimental–research activities.